2017
DOI: 10.1177/1541344617715710
|View full text |Cite
|
Sign up to set email alerts
|

Transformative Learning in Medical Education

Abstract: This longitudinal study followed the clinical learning journey of 20 medical students over 4 years, from the beginning of their clinical immersion, through one of the three different clinical placement models: block rotation, longitudinal integrated clerkship, or community- and hospital-integrated learning, and then into Year 4 and the intern year postgraduation. This study explored how these different contexts can influence the process of transformative learning. The results identified six well-defined change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 32 publications
(48 reference statements)
1
23
0
Order By: Relevance
“…In the findings, PSTs' changes in the way they see themselves involve becoming aware of their own strengths and weaknesses as a teacher. This means that PSTs experience self-awareness which supports a study from Greenhill et al (2018) that changes in perspective include self-awareness. Awareness of their strengths enhances PSTs' confidence, while awareness of their weaknesses urges them to learn more to become a better teacher.…”
Section: Discussionsupporting
confidence: 75%
“…In the findings, PSTs' changes in the way they see themselves involve becoming aware of their own strengths and weaknesses as a teacher. This means that PSTs experience self-awareness which supports a study from Greenhill et al (2018) that changes in perspective include self-awareness. Awareness of their strengths enhances PSTs' confidence, while awareness of their weaknesses urges them to learn more to become a better teacher.…”
Section: Discussionsupporting
confidence: 75%
“…Transformative learning within service-based roles has been repeatedly demonstrated within medical education [ 23 ]. Context and environment are integral to facilitating this, with safe learning environments that promote self-reflection and encourage the learner to reframe their thinking viewed as the most effective [ 24 ]. Therefore, perhaps the transformative learning that occurred may be partially attributed to the volunteering programme creating an appropriate environment for this to occur.…”
Section: Year Groupmentioning
confidence: 99%
“…The studies reported the implementation of specific clinical placement models to increase placement capacity [ 49 ], while others reflected on models for enhance consistency of the clinical environment and continued patient care [ 53 ]. Greenhill, et al [ 35 ] report that their clinical placement model allowed students an opportunity to access diverse patient conditions.…”
Section: Discussionmentioning
confidence: 99%